TEMA, CITRA DAN GAYA "DAY CARE, PRESCHOOL and BOUTIQUE": Fasilitas bagi Kanak-Kanak dan Balita di Lingkungan Apartemen di Jakarta - Gratia Tari; Tri Alnoz Kalla; Okki Pratiwi; Yuke Adriati (Jurnal Dimensi Seni Rupa dan Desain, 2007)
AbstractThe construction of condominiums which are progressively blooming at this time demons the investor to provide service by providing facilities which are needed Ibr the comfbrt and welfare of' living of the occupants. Among others, one requiredjaci lily is public space. Facilityfbr pre school also requires special attention because this matter is related to the spiritual and physical development or the .younger generation. And of course, as well as for emotional and social activities.keyword: theme, style and image, chikfren playground, preschool, apartmentAbstrakPembangunan rumah susun yang semakin berkembang saat ini menuntut investor untuk meningkatkan pelayanan dengan mengaciakan fasilitas yang diperlukan untuk kenyamanan penghuninya. Fasilitas itu diantaranya ad alah ruang publik.Fasilitas untuk anak-anak pra sekolah perlu mendapat perhatian khusus, karena hal ini berkaitan clengan perkembangan fisik kognitif, emosi maupun sosial.